Tactics for Twenty20 cricket - Silva, Rajitha M.; Perera, Harsha; Davis, Jack; Swartz, Tim B. (South African Statistical Journal, 2016)
This paper explores two avenues for the modification of tactics in Twenty20 cricket. The first idea is based on the realisation that wickets are of less importance in Twenty20 cricket than in other formats of cricket (e.g. one-day cricket and Test cricket). A consequence is that batting sides in Twenty20 cricket should place more emphasis on scoring runs and less emphasis on avoiding wickets falling. On the flip side, fielding sides should place more emphasis on preventing runs and less emphasis on taking wickets. Practical implementations of this general idea are obtained by simple modifications to batting orders and bowling overs. The second idea may be applicable when there exists a sizeable mismatch between two competing teams. In this case, the weaker team may be able to improve its win probability by increasing the variance of run differential. A specific variance inflation technique which we consider is increased aggressiveness in batting.